Comunidade de insetos associados aos sicônios de três espécies de figueiras no Pantanal Sul Matogrossense - Costa, Priscila Canesqui da (2010)
Syconia of fig trees present a diverse interaction with different groups of organisms. In this study we characterized insect community associated with three fig species in the region of Miranda/Abobral, Pantanal Sul matogrossense, obtaining data about species richness and abundance of these insects. We verified the specificity of these insects in regard to hosts and tested whether the size and number of flowers in the syconium determine species richness and abundance of insects in the syconia. We found 31 morpho-species of insects in the syconia of the three hosts. Syconia of Ficus obtusifolia had the highest richness (N = 18) and highest number of species co-occurring in the same syconia. Seven insect species were found sharing hosts. Mean abundance and species richness of insects in syconia of F. obtusifolia were significantly higher than in F. pertusa and F. luschnathiana what was related to the higher volume and number of flowers in the syconia of this fig tree. Our data may help in understanding the diversity and distribution of the insects associated with syconia of fig trees in the neotropical region. Papers that study Ficus insects associated system are important to show how these interactions occur in distinct fig trees and in different localities.